PERAN AGAMA DALAM PROSES REKRUTMEN TENAGA PENDIDIK DI PENDIDIKAN ISLAM - Tulili, Ammalia; Jamilus, Jamilus (J-KIP (Jurnal Keguruan dan Ilmu Pendidikan), 2025)
Education is the foundation of national development. Through education, individuals can develop their potential, understand social values, and contribute to the progress of society. Quality education emphasizes not only academic aspects but also the formation of character and individual morality. In this regard, Islamic education plays a very important role because it integrates values with general knowledge. Islamic education focuses not only on the transfer of knowledge but also on the development of solid character. In the Quran, Allah SWT says, "And indeed, We have created man in the best stature" (QS. At-Tin: 4). This indicates that the goal of Islamic education is to optimize the best potential of each individual. However, despite the importance of Islamic education, the recruitment process for educators still faces major challenges, such as the lack of qualified educators in both academic and religious understanding. Additionally, many Islamic schools struggle to attract quality educators due to low salaries and inadequate facilities offered. This situation has the potential to diminish the quality of education provided to students. To address these challenges, efforts must be made to improve the recruitment quality of educators through training and professional development for teachers. Thus, Islamic education can optimally function in shaping a generation that is academically intelligent and possesses strong character and noble morals.